Unlocking Indonesia's Maritime Potential: Optimizing Hub Port Development using a Principal Component Analysis and K-Means Clustering - Purnama, Dwi Adi; Marifa, Putri Citra; Shinta, Riadho Clara (TALENTA Publisher, 2025)
Indonesia as a maritime country, most of the transportation in Indonesia is carried out by using sea transportation around 88%. However, the Logistics Performance Index (LPI) of Indonesia is alarming and declining from 3.15 in 2018 to 3.0 in 2023, particularly in Timeliness (3.7 to 3.0) and Tracking & Tracing (3.3 to 3.0). Therefore, it needs a comprehensive improvement strategy, especially to optimize the hub port connectivity. This study would like to establish the new hub port connectivity in Indonesia to increase the effectiveness and efficiency of the port. This study use Principle Component Analysis (PCA) to determine the variable, eliminate the correlation among variables to obtain the new variables as the clustering determinants factor, and use Clustering K-Means to group similar characteristics of the alternative port that can be used as the main port. The result of Principle Component Analysis (PCA) which has gained new variables are regional spatial system, national transportation system, national defense, operational cost, and port services. The result of K-Means Clustering, Tanjung Priok, Panjang, Tanjung Emas, Tanjung Perak, Palembang, Teluk Bayur, and Belawan are the main port or hub port connectivity to increase the effectiveness and efficiency in the sea transportation. Tanjung Priok and Panjang can connect Java and Sumatra, while Tanjung Emas and Tanjung Perak can link Java and South Kalimantan. Palembang, Teluk Bayur, and Belawan can also play important roles in their respective regions. By investing in infrastructure and improving connectivity, Indonesia can enhance the efficiency and competitiveness of its maritime trade.